(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
This research focuses on an environmental and economic aspect, as it depends on using the harmful water hyacinth weed as an effective material to product the biopolymer "polyhydroxybutyrate: PHB" by Bacillus subtilis. The samples were processed and digested to extract the polymer polyhydroxybutyrate (PHB) using chloroform method. Some tests were carried out to confirm the identity of this polymer, such as measuring the melting point of the product and studying the functional groups of the extracted PHB using the Fourier-transform infrared spectroscopy (FTIR). The results obtained by the extracted polymer from the water hyacinth weed showed conformity to the referential PHB polymer tests, which shows the importance of this research in determining a way to get rid of this harmful weed, which is an environmental problem and a large economic burden by investing it in the production of biopolymer PHB.